Colonization With Antibiotic-Resistant Gram-Negative Bacteria in Population-Based Hospital and Community Settings in Chile. (October 2020) - Bralic, Rafael Araos; Peters, Anne; Sanchez, Felipe; Alvares, Danilo; Rivas, Lina; Spencer, Maria; Martinez, Rodrigo; Moya, Francisco; Rojas, Loreto; Rioseco, Maria Luisa; Rojas, Pamela; Usedo, Pedro; et al.
Abstract : Background: Estimating the burden of intestinal colonization with antibiotic-resistant gram-negative bacteria (AR-GNB) is critical to understanding their global epidemiology and spread. We aimed to determine the prevalence of, and risk factors for, intestinal colonization due to AR-GNB in population-based hospital and community settings in Chile. Methods: Between December 2018 and May 2019, we enrolled randomly selected hospitalized adults in 4 tertiary-care public hospitals (Antofagasta, Santiago, Curico and Puerto Montt), and adults residing in a community-based cohort in the rural town of Molina. Following informed consent, we collected rectal swabs and epidemiological information through a standardized questionnaire. Swabs were plated onto MacConkey agar with 2 µg/mL ciprofloxacin or ceftazidime. All recovered morphotypes were identified, and antibiotic susceptibility testing was performed via disk diffusion. The primary outcome was the prevalence of colonization with fluoroquinolone (FQ)- or third-generation cephalosporin (3GC)–resistant GNB. The secondary outcome was the prevalence of colonization with multidrug-resistant (MDR) GNB, defined as GNB resistant to ≥3 antibiotic classes. Categories were not mutually exclusive. Bivariate and multivariate analyses were performed to describe risk factors for colonization with these categories. Results: In total, 775 hospitalized adults and 357 community participants were enrolled, with a median age of 60 years (IQR, 42–72) and 55 years (IQR, 48–62) years, respectively. Among hospitalized participants, the prevalence of colonization with FQ- or 3GC-resistant GNB was 47% (95% CI, 43%–50%) and 41% (95% CI, 38%–45%), respectively, whereas the prevalence of MDR-GNB colonization was 27% (95% CI, 24%–31%). In the community setting, the prevalence of colonization with either FQ-, 3GC-resistant GNB, or MDR-GNB was 40% (95% CI, 34%–45%), 29% (95% CI, 24%– 34%), and 5% (95% CI, 3%–8%), respectively. Independent risk factors for hospital MDR-GNB colonization included the hospital of admission, unit of hospitalization (intensive care units carried the highest risk), in-hospital antimicrobial exposure, comorbidities (Charlson index), and length of stay. In the community setting, recent antibiotic exposure (<3 months) predicted colonization with either FQ- or 3GC-resistant GNB, and alcohol consumption was inversely associated with MDR GNB colonization. Conclusions: A high burden of colonization with AR-GNB was observed in this sample of hospitalized and community-dwelling adults in Chile. The high burden of colonization with GNB resistant to commonly used antibiotics such as FQ and 3GC found in community dwellers, suggests that the community may be a relevant source of antibiotic resistance. Efforts to understand relatedness between resistant strains circulating in the community and the hospital are needed. Funding: None Disclosures: None